The purposes and processes of master's thesis supervision: a comparison of Chinese and Dutch supervisors. Issue 5 (2nd September 2016) - Hu, Yanjuan; van der Rijst, Roeland Matthijs; van Veen, Klaas; Verloop, Nico
ABSTRACT: The number of international Chinese students enrolled in research programmes in Western universities is growing. To provide effective research supervision to these students, it is helpful to understand the similarities and differences in the supervision process between the host country and their home country. We explored which learning outcomes supervisors of master's theses aim for in two cultures, China and the Netherlands, and how they help their students to achieve these learning outcomes. Semi-structured interviews with 10 Chinese and 10 Dutch supervisors revealed, besides a strong resemblance, some clear differences between the two groups. For example, the Chinese supervisors aim to prepare their students for future jobs and use explicit assessment and regulation to monitor student progress, while the Dutch supervisors aim to enhance student well-being and use implicit regulation, emotional support and frequent posing of questions to facilitate student learning. Implications for cross-cultural and international education are provided.